IMPLEMENTASI API RESTFUL DENGAN JSON WEB TOKEN (JWT) PADA APLIKASI E-COMMERCE THRIFTY SHOP UNTUK OTENTIKASI DAN OTORISASI PENGGUNA - Nashikhuddin, Ahmad Yahya; Karaman, Jamilah; Litanianda, Yovi (Universitas Methodist Indonesia, 2023)
User authentication and authorization play a vital role in securing sensitive data within applications. E-commerce applications, in particular, require robust authentication and authorization methods to safeguard the confidentiality and integrity of exchanged data. JSON Web Token (JWT) has emerged as a popular authentication mechanism for securing data transmission over networks. This paper explores the implementation of JWT in a RESTful API to achieve user authentication and authorization in an E-commerce application. The objective of this study is to analyze the implementation of JWT in a RESTful API for user authentication and authorization within an E-commerce context. The detailed implementation of JWT in the Thrifty Shop application is discussed, encompassing its utilization for user authentication and authorization. Additionally, the benefits derived from employing JWT in the Thrifty Shop E-commerce application are explored. In conclusion, the implementation of JSON Web Token (JWT) in a RESTful API proves to be an effective approach for user authentication and authorization in E-commerce applications. The use of JWT ensures that only authenticated users gain access to sensitive data, thus enhancing the security of the Thrifty Shop E-commerce application. This implementation can serve as a model for other E-commerce applications seeking to bolster their security measures.